Unequal freedom: how race and gender shaped American citizenship and labor - Glenn, Evelyn Nakano (Harvard University Press, 2002)
The inequalities that persist in America have deep historical roots. Evelyn Nakano Glenn untangles this complex history in a unique comparative regional study from the end of Reconstruction to the eve of World War II. During this era the country experienced enormous social and economic changes with the abolition of slavery, rapid territorial expansion, and massive immigration, and struggled over the meaning of free labor and the essence of citizenship as people who previously had been excluded sought the promise of economic freedom and full political rights.After a lucid overview of the concepts of the free worker and the independent citizen at the national level, Glenn vividly details how race and gender issues framed the struggle over labor and citizenship rights at the local level between blacks and whites in the South, Mexicans and Anglos in the Southwest, and Asians and haoles (the white planter class) in Hawaii. She illuminates the complex interplay of local and national forces in American society and provides a dynamic view of how labor and citizenship were defined, enforced, and contested in a formative era for white-nonwhite relations in America.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amériques; approches et analyses; cours; discipline; droits des femmes*; droits des personnes; histoire et politique; intersectionnalité; inégalités; pol4212; premier cycle; périodes historiques; racisme; racisme systémique; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis; études critiques de la race; études de genres

Loving internationalism: The emotion culture of transnational women's organizations, 1888-1945 - Taylor, Verta; Rupp, Leila (Mobilization: An International Quarterly, 2002)
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; allemagne; amériques; angleterre; discipline; droits des femmes*; europe; femmes* trans; france; militance; pays-bas; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; états-unis

La violence nazie, une généalogie européenne - Traverso, Enzo (La Fabrique, 2002)
La violence nazie ne doit rien au hasard: elle a une généalogie, qui n'est pas spécifiquement allemande, et un laboratoire, l'Europe libérale du XIXe siècle.Les camps d'extermination sont l'aboutissement d'un long processus de déshumanisation et d'industrialisation de la mort, amorcé par la guillotine et qui a progressivement intégré la rationalité du monde moderne, celle de l'usine, de la bureaucratie, de la prison. On peut trouver les origines culturelles du nazisme dans le "racisme de classe" qui triomphe après la Commune, dans le discours impérialiste sur l'"extinction des races inférieures" visant à légitimer les génocides coloniaux, enfin dans l'émergence d'une nouvelle image du juif- axée sur la figure de l'intellectuel - comme métaphore d'une maladie du corps social.Le nazisme réalisera la convergence entre ces différentes sources matérielles et idéologiques. Auschwitz se révèle ainsi - et c'est là que réside, selon Enzo Traverso, sa singularité - comme la synthèse d'un ensemble de modes de pensée, de domination et d'extermination profondément inscrits dans l'histoire occidentale.
Keywords: 1900-1999; 1930-1939; 1940-1949; allemagne; approches et analyses; cours; discipline; europe; histoire; histoire et politique; pol5480; premier cycle; périodes historiques; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences